An overview of learning methodology for clinical pharmacokinetics course during the COVID-19 pandemic / Hannani Mawarddah Muhammad Abdul Hafidz, Nur Wahida Zulkifli and Farhana Fakhira Ismail - Muhammad Abdul Hafidz, Hannani Mawarddah; Zulkifli, Nur Wahida; Ismail, Farhana Fakhira (UiTM Press, 2023)
Due to the Covid-19 pandemic, the clinical pharmacokinetics course had to undergo a few modifications to its curriculum content. During the curriculum realignment, the Faculty of Pharmacy at UiTM Puncak Alam was obliged to adapting rapidly to these conditions by developing a few new strategies by implementing interesting learning methodologies that can suit students during the pandemic. In addition, despite being an interesting course, students are still afraid of clinical pharmacokinetics, thinking it difficult to understand. This study reviewed students’ perceptions and satisfaction with the course and examples of learning methodologies which are suitable for pharmacokinetics course.